2021
DOI: 10.3390/biom11020176
|View full text |Cite
|
Sign up to set email alerts
|

CAPE and Neuroprotection: A Review

Abstract: Propolis, a product of the honey bee, has been used in traditional medicine for many years. A hydrophobic bioactive polyphenolic ester, caffeic acid phenethyl ester (CAPE), is one of the most extensively investigated active components of propolis. Several studies have indicated that CAPE has a broad spectrum of pharmacological activities as anti-oxidant, anti-inflammatory, anti-viral, anti-fungal, anti-proliferative, and anti-neoplastic properties. This review largely describes CAPE neuroprotective effects in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 85 publications
1
22
0
Order By: Relevance
“…Our findings are in line with the results of Balaha et al who clarified in their study the potentiality of CAPE against Cd-induced toxicity. This is demonstrated in certain antioxidant effect of CAPE on tissue damage [46]. This is also in agreement with the results of Abdallah et al who affirmed that a section in testes of a rat treated with Cd and CAPE showed an increase of spermatogenic cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in line with the results of Balaha et al who clarified in their study the potentiality of CAPE against Cd-induced toxicity. This is demonstrated in certain antioxidant effect of CAPE on tissue damage [46]. This is also in agreement with the results of Abdallah et al who affirmed that a section in testes of a rat treated with Cd and CAPE showed an increase of spermatogenic cells.…”
Section: Discussionsupporting
confidence: 92%
“…who clarified in their study the potentiality of CAPE against Cd-induced toxicity. This is demonstrated in certain antioxidant effect of CAPE on tissue damage [ 46 ]. This is also in agreement with the results of Abdallah et al.…”
Section: Discussionmentioning
confidence: 99%
“…Antidepressant and anxiolytic properties as well as beneficial effects in Parkinson’s and Alzheimer’s diseases were ascribed to resveratrol, the most studied phenolic compound in wine [ 8 , 9 ]. Additionally, caffeic acid and its natural derivative, caffeic acid phenetyl ester (CAPE), have numerous neuroprotection effects [ 10 ] against cancer and others [ 11 ]. Other phenols, including catechins, have remarkable neuroprotective activity [ 12 ] to such an extent that new therapeutical targets were proposed [ 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin and related compounds including caffeic acid phenethyl ester (CAPE), and caffeic acid ( Kabala-Dzik et al, 2017 ) are bioactive compounds mainly derived from natural sources and known for years for their pleiotropic effects ( Figure 1 ). These compounds show anti-viral, anti-fungal, anti-microbial and anti-tumor effects ( Chiao et al, 1995 ; Beauregard et al, 2015 ; Balaha et al, 2021 ), mainly ascribable to anti-inflammatory and antioxidant activities. Curcumin product is used as cosmetic additive and dietary supplement and as herbal medicine ( Hassanalilou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%